Management of Capital in Georgian State-owned Medical Organizations - Mamukelashvili, Ioseb; Merabishvili, Ketevan (Archives of Business Research, 2018)
Management of medical organizations is a peculiar process because, on one hand, medical firms fulfill essential social needs by providing medical services to the population and, on the other hand, they have to be financially sound in order to keep functioning. We obtained financial statements of three major state-owned hospitals in Tbilisi and formed conclusions based on financial statement analysis. The Capital Ratio formula was developed based on Myer’s and Majluf’s pecking order theory and our hypothesis was confirmed. We concluded that the three hospitals are mainly using their own equity and should pursue long-term financing in order to finance their capital expenditures. Series of tests also confirmed that higher debt ratio would result in higher revenue for the three state-owned hospitals (74% regression coefficient). Furthermore, we have determined that financial statement analysis should be used to make strategic decisions. In particular, the three state-owned hospitals should pay particular attention to short-term liquidity.